Nivel de información del plan de egreso por pacientes de traumatología del hospital general Latacunga, noviembre 2017- marzo 2018”. - Beltrán Neto, Stefany Carolina (2018)
This project of investigation was conducted at the General Hospital Latacunga in the traumatology area, this study was descriptive, qualitative and transversal, the observation guide was one of the instruments that were used, it was applied to the Nursing professionals and a survery directed to patients who are referred with egress. The study population was 13 nurses in addition, 28 patients who had hospital sendoff. It was concluded that the nursing professional does not provide complete information to the user in reference to the leave-taking plan as they are done routinely. The proposal was the educational egress plan in a detailed way, and thus the understanding of the user is recorded; which will be socialized to the staff working in that area.